Manajemen Laba Dan Kinerja Keuangan Perusahaan Pengakuisisi Sebelum Dan Sesudah Merger Dan Akuisisi Di Indonesia - Alwan Sri Kustono; Agnes Sindhy Pikatan (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2012)
The study examine the earnings management practice in aquirer companies before and after mergers and acquisitions. It also show the difference financial performance. The purpose of this study was to prove the existence of the practice earnings management by the acquirer in the period prior to the mergers and acquisitions. this study also aimed to see whether there differences in the financial performance of the acquirer after the merger policy and acquisition of the manufacturing companies listed on the Stock Exchange over a period reporting year 2006-2008. The sample in this study are 13 manufacturing companies listed on the Indonesia Stock Exchange in reporting mergers and acquisitions 2006-2008. The conclusion of this study is there is no strong evidence through discretionary accrual indicating that earnings management measures made by the acquirer in the period prior to the merger and acquisitions and also no significant differences in financial performance afterimplementation of mergers and acquisitions on the acquirer.